Top Secret Twenty-One: First Edition - Evanovich, Janet (New York : Bantam Books, 2014)
"Trenton, New Jersey's favorite used car dealer, Jimmy Poletti, was caught selling a lot more than used cars out of his dealerships. Now he's out on bail and has missed his date in court--and bounty hunter Stephanie Plum is looking to bring him in. Leads are quickly turning into dead ends, and all too frequently into dead bodies. Even Joe Morelli, the city's hottest cop, is struggling to find a clue to the suspected killer's whereabouts. To top things off, Ranger--resident security expert and Stephanie's greatest temptation--has been the target of an assassination plot. He's dodged the bullet this time, but if Ranger wants to survive the next attempt on his life, he'll have to enlist Stephanie's help. Death threats, highly trained assassins, highly untrained assassins and Stark Street being overrun with a pack of feral Chihuahuas are all in a day's work for Stephanie Plum"--
Library Journal Prepub Alert
Adult.
Adult.
Keywords: Plum, Stephanie (Fictional character) -- Fiction; Bounty hunters -- Fiction; Mystery fiction; Trenton (N.J.) -- Fiction